Persepsi Komunikasi Visual Terhadap Media Promosi BRT (Bus Rapid Transit) Trans Jateng Koridor Purwokerto - Purbalingga - Fauzan Romadlon; Pungky Febi Arifianto; Nofrizaldi Nofrizaldi (Universitas Multimedia Nusantara, 2021)
Bus Rapid Transit (BRT) is one of public transportation modes in Purwokerto-Purbalingga that has a visual communication element as form as transit ads for a tourism promotion media. This study aims to analyze public perceptions in terms of the effectiveness of visual communication of the promotional media. This study uses a Likert scale to assess and ANOVA to analyze the results. The results of the study indicate that the perception criteria are based on demographic factors, especially gender and job type. Men and women have different perspectives regarding the visual communication design that is applied in BRT. This study also illustrates that the expected promotion of the community as general is increasingly diverse. Promotion is expected not to be limited to tourism promotion, it is also possible to promote culinary, batik promotion, and invitations to use public transportation to campaign to prevent corrupt behavior. Keywords: perception; promotion media; visual communication; bus rapid transit; Purwokerto-Purbalingga.